Is accruals quality a priced risk factor? - Core, John E.; Guay, Wayne R.; Verdi, Rodrigo (Journal of Accounting and Economics, 2008)
In a recent and influential empirical paper, Francis, LaFond, Olsson, and Schipper (FLOS) [2005. The market pricing of accruals quality. Journal of Accounting and Economics 39, 295–327] conclude that accruals quality (AQ) is a priced risk factor. We explain that FLOS’ regressions examining a contemporaneous relation between excess returns and factor returns do not test the hypothesis that AQ is a priced risk factor. We conduct appropriate asset-pricing tests for determining whether a potential risk factor explains expected returns, and find no evidence that AQ is a priced risk factor.